2017
DOI: 10.1002/bmc.3888
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 reaction phenotyping and inhibition and induction studies of pinostrobin in human liver microsomes and hepatocytes

Abstract: Pinostrobin (PI, 5-hydroxy-7-methoxyflavanone) is a natural flavonoid known for its rich pharmacological activities. The objective of this study was to identify the human liver cytochrome P450 (CYP450) isoenzymes involved in the metabolism of PI. A single hydoxylated metabolite was obtained from PI after an incubation with pooled human liver microsomes (HLMs). The relative contributions of different CYP450s were evaluated using CYP450-selective inhibitors in HLMs and recombinant human CYP450 enzymes, and the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Cytochrome P450 (CYP450) plays an important role in the phase I metabolism of a wide variety of compounds (endogenous and exogenous) . Moreover, CYP1A2, CYP2C9, and CYP2E1 were the main metabolic subtype of CYP450 for flavone . And transmethylase, sulfotransferase (ST), and UDP-glucuronosyltransferases (UGTs) were the main metabolic enzymes of phase II.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cytochrome P450 (CYP450) plays an important role in the phase I metabolism of a wide variety of compounds (endogenous and exogenous) . Moreover, CYP1A2, CYP2C9, and CYP2E1 were the main metabolic subtype of CYP450 for flavone . And transmethylase, sulfotransferase (ST), and UDP-glucuronosyltransferases (UGTs) were the main metabolic enzymes of phase II.…”
Section: Resultsmentioning
confidence: 99%
“…33 Moreover, CYP1A2, CYP2C9, and CYP2E1 were the main metabolic subtype of CYP450 for flavone. 34 And transmethylase, 35 sulfotransferase (ST), 36 and UDP-glucuronosyltransferases (UGTs) 37 were the main metabolic enzymes of phase II. Furthermore, UGT1A1, UGT1A3, UGT1A9, UGT1A10, and UGT2B7 mainly participated in glucuronide conjugation reaction of flavone.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Hepatic CYP1A2, CYP2C9, and CYP2E1 were the primary enzymes responsible for the formation of the hydroxylated metabolite of pinostrobin. 39 In this study, we investigated the in vitro effects of pinostrobin on hepatic cell line. We demonstrated inhibition of PCSK9 gene expression by pinostrobin at concentrations 20−40 μM, which are used in vitro cell culture system, though it is higher than what can be achieved in vivo.…”
Section: ■ Discussionmentioning
confidence: 99%
“…In in vitro studies, it has been reported that pinostrobin was converted into hydroxylated metabolite of pinostrobin by human liver microsomes. Hepatic CYP1A2, CYP2C9, and CYP2E1 were the primary enzymes responsible for the formation of the hydroxylated metabolite of pinostrobin . In this study, we investigated the in vitro effects of pinostrobin on hepatic cell line.…”
Section: Discussionmentioning
confidence: 99%
“…Tangeretin was previously demonstrated to induce the activity of CYP3A4, a major isoenzyme of CYP450 and responsible for the metabolism of ligustrazine. 17,18 Therefore, it was speculated that the coadministration of tangeretin with ligustrazine might induce changes in the pharmacokinetics of ligustrazine via inducing CYP3A4, which was investigated in this study.…”
Section: Introductionmentioning
confidence: 99%